To find the second term of the geometric sequence given by the recursive formula \(a_n = Z \cdot a_{n-1}\), we need to clarify both the initial term and the common ratio. From your message, it appears that the first term \(a_1 = 5\) and there is an inconsistency with the common ratio, which seems to be denoted as \(Z\) without a specified value.
If we assume \(Z\) is not defined and you meant to specify a value for it, please provide that value. If let's say we assume \(Z = 2\) (as the text suggests), we can proceed with the calculation:
- \(a_1 = 5\)
- \(a_2 = Z \cdot a_1 = 2 \cdot 5 = 10\)
Thus, if \(Z\) is 2, the second term of the sequence is:
\[ a_2 = 10 \]
If you meant \(Z\) to be a different value, please specify, and I can recalculate.